Impact of graphite particle on milling of Al/15Al2O3 and Al/15Al2O3/5Gr composites. (1st November 2016) - Premnath, Arun
ABSTRACT: Hybrid Metal Matrix Composites (MMCs) are a new class of composites, formed by a combination of the metal matrix and more than one type of reinforcement having different properties. Machining of MMCs is a difficult task because of its heterogeneity and abrasive nature of reinforcement, which results in excessive tool wear and inferior surface finish. This paper investigates experimentally the addition of graphite (Gr) on cutting force, surface roughness and tool wear while milling Al/15Al2 O3 and Al/15Al2 O3 /5Gr composites at different cutting conditions using tungsten carbide (WC) and polycrystalline diamond (PCD) insert. The result reveals that feed has a major contribution on cutting force and tool wear, whereas the machined surface roughness was found to be more sensitive to speed for both composite materials. The incorporation of graphite reduces the coefficient of friction between the tool–workpiece interfaces, thereby reducing the cutting force and tool wear for hybrid composites. The surface morphology and worn tool are analyzed using scanning electron microscope (SEM). The surface damage due to machining extends up to 200 µm for Al/15Al2 O3 /5Gr composites, which is beyond 250 µm for Al/15Al2 O3 composites.